2007
DOI: 10.1074/jbc.m608327200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repression of Matrix Metalloproteinase Gene Expression by the Orphan Nuclear Receptor NURR1 in Cartilage

Abstract: The NR4A orphan receptors (Nur77, NURR1, and NOR-1) are emerging as key regulators of cytokine and growth factor action in chronic inflammatory diseases. In this study, we address the role of these receptors in cartilage homeostasis during inflammatory joint disease. We document for the first time expression of the NR4A receptors in osteoarthritic cartilage. Relative to Nur77 and NOR-1, NURR1 is expressed at the highest level and correlates with cyclooxygenase-2 levels in cartilage. Consistent with this observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 83 publications
7
76
0
Order By: Relevance
“…Increased MMP-13 expression was accompanied by increased cleavage of collagen and decreased proteoglycan synthesis in cartilage explant cultures. How the divergent synthesis of MMP-1 and -13 is regulated remains unknown, but we have previously reported that up-regulation of the nuclear orphan receptor NURR1 (NR4A2) in OA cartilage causes similar divergent effects, suggesting that the mechanism of PGE 2 on MMP-1 and MMP-13 may be a result of NURR1 activation (NR4A2) (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased MMP-13 expression was accompanied by increased cleavage of collagen and decreased proteoglycan synthesis in cartilage explant cultures. How the divergent synthesis of MMP-1 and -13 is regulated remains unknown, but we have previously reported that up-regulation of the nuclear orphan receptor NURR1 (NR4A2) in OA cartilage causes similar divergent effects, suggesting that the mechanism of PGE 2 on MMP-1 and MMP-13 may be a result of NURR1 activation (NR4A2) (20).…”
Section: Discussionmentioning
confidence: 99%
“…RNA content was estimated using a spectrophotometer, the 260:280 ratio for purified RNA was ϳ2.0. The integrity of RNA was confirmed using 1% formaldehyde agarose gel electrophoresis (19,20).…”
Section: Rna Extraction From Articular Chondrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…40,42,46 We have previously demonstrated that NURR1 is the major cytokine-regulated member of the NR4A subfamily in inflamed human synovium and cartilage. 38,39,41,44,46 NURR1 characteristically regulates target gene expression through interaction with a specific consensus sequence in the promoters of target genes, known as the nerve growth factor-induced clone B response element (NBRE). 47 Phosphorylation or interaction with other transcription factors and co-regulatory proteins can also influence NURR1-mediated gene regulation.…”
mentioning
confidence: 99%
“…Adenosine, acting in particular through the A2a receptor and NR4A2 has also been shown to mediate the antiinflammatory effects of methotrexate in rheumatoid arthritis [45]. NR4A2 also mediates the repression of matrix metalloproteinases during inflammation [46].…”
Section: Discussionmentioning
confidence: 99%